Air conditioning system design - Legg, Roger (Butterworth-Heinemann, an imprint of Elsevier, 2017)
Air Conditioning System Design summarizes essential theory and then explains how the latest air conditioning technology operates. Load calculations, energy efficiency, and selection of technology are all explained in the context of air conditioning as a system, helping the reader fully consider the implications of design decisions. Whether users need to figure out how to apply their mechanical engineering degree to an air conditioning design task or simply want to find out more about air conditioning technology for a research project, this book provides a perfect guide.